2018
DOI: 10.1007/s00240-018-1067-5
|View full text |Cite
|
Sign up to set email alerts
|

Oxalate transport by the mouse intestine in vitro is not affected by chronic challenges to systemic acid–base homeostasis

Abstract: In rats, we recently showed how a chronic metabolic acidosis simultaneously reduced urinary oxalate excretion and promoted oxalate secretion by the distal colon leading to the proposition that acid-base disturbances may trigger changes to renal and intestinal oxalate handling. The present study sought to reproduce and extend these observations using the mouse model, where the availability of targeted gene knockouts (KOs) would offer future opportunities to reveal some of the underlying transporters and mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
1
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 67 publications
2
1
0
1
Order By: Relevance
“…3). Again, this was consistent with our recent reports on the magnitude and direction of epithelial oxalate and sulfate transport by the mouse cecum (84,87), but the fluxes of both these anions were also entirely independent of SAT-1. Dawson et al (17) had previously shown a significant 47% reduction in oxalate uptake by BLMVs from the SAT-1-KO cecum in vitro, and in addition, the cecal contents of these KO Table 1.…”
Section: Oxalate and Sulfate Secretion By The Cecumsupporting
confidence: 93%
See 1 more Smart Citation
“…3). Again, this was consistent with our recent reports on the magnitude and direction of epithelial oxalate and sulfate transport by the mouse cecum (84,87), but the fluxes of both these anions were also entirely independent of SAT-1. Dawson et al (17) had previously shown a significant 47% reduction in oxalate uptake by BLMVs from the SAT-1-KO cecum in vitro, and in addition, the cecal contents of these KO Table 1.…”
Section: Oxalate and Sulfate Secretion By The Cecumsupporting
confidence: 93%
“…2A) and a robust absorption of sulfate (Fig. 2B) under symmetrical, short-circuited conditions in vitro, in agreement with our recent reports of oxalate (85,87,88) and sulfate (86) fluxes by this segment. Unexpectedly, SAT-1 was not required to sustain the transport of either anion, contrary to the notion of SAT-1 as a SO 4 2Ϫ /oxalate exchanger facilitating intestinal oxalate secretion and sulfate absorption (58).…”
Section: Oxalate Secretion and Sulfate Absorption By The Distal Ileumsupporting
confidence: 92%
“…In the mouse distal ileum, oxalate transport has been shown to occur through the bicarbonate chloride exchangers, PAT1 (Slc26a6) and DRA (Slc26a3), contributing to secretion and absorption, respectively (Freel et al, 2006(Freel et al, , 2013. At least in other parts of the small intestine, PAT1 and DRA are known to be functionally and physically associated with NHE3 (Musch et al, 2009;Seidler & Nikolovska, 2019;Seidler et al, 2008;Singh et al, 2010;Walker et al, 2008;Xu et al, 2018); however, this study suggests NHE3 is not integral to the oxalate transport mechanism in murine distal ileum and basal oxalate fluxes were not dissimilar to what has previously been reported (Whittamore et al, , 2018Whittamore & Hatch, 2019). This occurred in the context of reduced G T in the NHE3 KO distal ileum.…”
Section: The Distal Ileummentioning
confidence: 63%
“…Jika napas sulit, berikan oksigen. Dapatkan bantuan medis (96,(193)(194)(195)(196)(197)(198)(199)(200)(201)(202)(203)(204)(205)(206)(207)(208)(209)(210)(211) . Catatan dokter : Ssetelah paparan inhalasi, amati selama 24 s.d 72 jam sebagai edema paru mungkin tertunda…”
Section: Bahayaunclassified